2011
DOI: 10.15288/jsad.2011.72.308
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-Year Alcohol-Consumption and Drinking-Problem Trajectories of Older Men and Women

Abstract: ABSTRACT. Objective: The aim of this study was to describe older adults' 20-year alcohol-consumption and drinking-problem trajectories, identify baseline predictors of them, and determine whether older men and women differ on late-life drinking trajectory characteristics and predictors. Method: Two-group simultaneous latent growth modeling was used to describe the characteristics and baseline predictors of older community-residing men's (n = 399) and women's (n = 320) 20-year drinking trajectories. Chi-square … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
69
5
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 58 publications
14
69
5
2
Order By: Relevance
“…A shorter time window for assessment may decrease the prevalence of use relative to a longer time window because it permits more time for a drinking occasion to occur; moreover, it may infl uence the average number of drinks per day because if no drinking is reported for the shorter time window, the average number of drinks per day is "zero," whereas a longer time window may yield a nonzero value if drinking occurs. The percentage of drinkers in our community sample was quite similar to that found in Brennan et al's (2011) community sample.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…A shorter time window for assessment may decrease the prevalence of use relative to a longer time window because it permits more time for a drinking occasion to occur; moreover, it may infl uence the average number of drinks per day because if no drinking is reported for the shorter time window, the average number of drinks per day is "zero," whereas a longer time window may yield a nonzero value if drinking occurs. The percentage of drinkers in our community sample was quite similar to that found in Brennan et al's (2011) community sample.…”
Section: Discussionsupporting
confidence: 85%
“…Contrary to these fi ndings, at the aggregate level, Platt et al (2010)-with a sample of 51-to 61-year-olds at baseline-reported a decline in the number of drinks consumed per day and an increase in abstainers across a 15-year period, with the greatest change occurring in the fi rst 5 years of the study, earlier than that reported by Brennan et al (2011). In a longitudinal study of middle-aged adults, Molander et al (2010) found that from age 53 (Time 1) to age 64 (Time 2), at the aggregate level, the average number of drinks per drinking day and heavy drinking decreased, but the frequency of drinking increased among both men and women.…”
Section: Alcohol Use In Middle-aged Adultscontrasting
confidence: 78%
See 3 more Smart Citations